Improving Perinatology Residents' Skills in Breaking Bad News: A Randomized Intervention Study - Maria Silvia Vellutini Setubal; Maria Ângela Reis Goes Monteiro Antonio; Eliana Martorano Amaral; John Boulet (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective Breaking bad news (BBN) is particularly difficult in perinatology. Previous research has shown that BBN skills can be learned and improved when taught and practiced. This project evaluated whether a structured training session would enhance perinatology residents' skills in BBN. Methods This was a randomized controlled intervention study with year 1 to 4 Perinatology residents from a medical school in Brazil, during the 2014/15 school year. A total of 61 out of 100 (61%) eligible residents volunteered to a structured training program involving communicating a perinatal loss to a simulated patient (SP) portraying the mother followed by the SP's immediatefeedback,bothvideo recorded. Later, residents were randomly assigned to BBN training based on a setting, perception, invitation, knowledge, emotion and summary (SPIKES) strategy with video reviews (intervention) or no training (control group). All residents returned for a second simulation with the same SP blinded to the intervention and portraying a similar case. Residents' performances were then evaluated by the SP with a checklist. The statistical analysis included a repeated measures analysis of covariance (RM-ANCOVA). Complementarily, the residents provided their perceptions about the simulation with feedback activities. Results Fifty-eight residents completed the program. The simulations lasted on average 12 minutes, feedback 5 minutes and SPIKES training between 1h and 2h30m. There was no significant difference in the residents' performances according to the SPs' evaluations (p = 0.55). The participants rated the simulation with feedback exercises highly. These educational activities might have offset SPIKES training impact. Conclusion The SPIKES training did not significantly impact the residents' performance. The residents endorsed the simulation with feedback as a useful training modality. Further research is needed to determine which modality is more effective.